(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
All patients admitted to the Intensive Care Unit of BSMMU between January 2006 and December 2006 on whom data had been entered into the study. A total of 473 admissions with complete records were available. Hospital mortality was 60.6%. Nonsurvivors were older than survivors and had longer ICU stays. Patients admitted from wards had a higher mortality than patients from the operating room/ recovery or the emergency department. Thirty-four percent of patients were in the ICU for >2 days, and they accounted for nearly 81% of bed occupancy. Early identification of patients at risk, both before admission and after discharge from the ICU, may allow treatment to decrease mortality. Research and resources may be best directed at patients who die, despite a relatively low predicted mortality. Many patients die after discharge from ICU and this mortality may be decreased by minimizing inappropriate early discharge to the ward, by the provision of high dependency and step-down units, and by continuing advice and follow-up by the ICU team after the patient has been discharged. DOI: http://dx.doi.org/10.3329/jbsa.v22i1.18095 Journal of BSA, 2009; 22(1): 12-15